PENGARUH KOMPENSASI, KOMPETENSI DAN TEKNOLOGI TERHADAP MOTIVASI YANG BERDAMPAK PADA KINERJA KARYAWAN DI KANTOR PUSAT PT TIMAH TBK - Riza Aprianto; Amri Amri; Adrian Radiansyah (JEM Jurnal Ekonomi dan Manajemen, 2020)
This study aims to analyze and determine the effect of compensation factors, competence and technology on motivation and the influence of motivational factors on performance, with employee respondents who work at the Head Office of PT TIMAH Tbk. The data is processed by path analysis. From the results of hypothesis testing, it is concluded that there is an effect of compensation, competence, IT technology on motivation, and motivation variables have an effect on performance. Based on the conclusion, the influence of competence has a very big influence on the motivation of employees at the PT TIMAH Tbk Head Office, for that it needs to be maintained and increase its influence on motivation again. In an effort to improve performance, it is advisable to management at the Head Office of PT TIMAH Tbk to be able to place the required employees according to their competencies so that organizational goals can be achieved effectively and efficiently. Further research is needed by adding other variables, in order to determine future policies.